A Review of Research on Classroom Management in Turkey. (13th May 2015) - Erdogan, Mehmet; Kurt, Abdulkadir
Abstract: This study aimed to review and critique classroom management research in Turkey, and present the emerging themes and findings of the selected studies on classroom management undertaken through 2002 to 2014. This paper reports on a content analysis of 46 classroom management research papers published in selected national and international journals and 8 peer-reviewed master/Phd thesis. Selection and then content analysis of the selected 54 studies in total were done in considering pre-determined criteria. Firstly, the findings indicated that teachers' ability to create this interactive classroom environment was influenced by some variables such as teacher beliefs and teachers' expectations of the students. Second, it demonstrated the complex nature of classroom management as it was investigated through a rich set of variables in the study. Third, it provided implications for teachers and teacher trainers on classroom management. Finally this study outlines the critical areas of research on classroom management and identifies areas of further research.